Lowering Regional Inflation? Improve Budget Absorption - Adrison, Vid (Economics and Finance in Indonesia, 2016)
The subnational government spending in Indonesia exhibit a highly skewed distribution, i.e., it is very low in the first two-quarters and then increases significantly in the last two-quarters. Such explosive pattern poses two disadvantages. First, the regional output will fall below its optimal level as the low government capital expenditure leads to a fewer provision of public goods. Second, a significant increase in government spending in the later quarter pushes the short run aggregate demand to the northeast and creates an inflationary pressure in the following quarters. In this study, we analyze the effect of quarterly regional government expenditure growth on regional inflation during 2010-2014. Using Arellano Bond GMM estimation, we find government expenditure growth leads to higher inflation in the same quarter. A percentage increase in non-capital expenditure spending results in a higher inflation than a percentage increase in capital spending.